Hearing loss is associated with increased stroke risk in the Dongfeng-Tongji Cohort. (June 2019) - Fang, Qin; Lai, Xuefeng; Yang, Liangle; Wang, Zhichao; Zhan, Yue; Zhou, Lue; Xiao, Yang; Wang, Hao; Li, Dan; Zhang, Kun; Zhou, Tao; Yang, Handong; et al.
Abstract: Background and aims: The evidence concerning the association between hearing loss and stroke is limited. We aimed to investigate the association of hearing loss with risk of stroke and its subtypes among the middle-aged and older Chinese population. Methods: We included 19, 238 participants aged 64.6 years from the Dongfeng-Tongji Cohort in 2013. Hearing loss was classified into normal, mild, moderate, severe or greater levels by the pure tone average at speech frequency and high frequency, respectively. We calculated the odds ratios of hearing loss and stroke by logistic regression models. Results: With the increase of hearing loss level, the prevalence risk of stroke has gradually increased. Compared with normal hearing, participants having severe or greater hearing loss had a higher stroke risk of 76% and 39% at speech frequency and at high frequency, respectively. Similarly, individuals with severe or greater hearing loss had an increased risk of ischemic stroke of 69% and 52% at speech frequency and high frequency, respectively; while severe or greater hearing loss was associated with about a 2-fold risk of hemorrhagic stroke than normal hearing only at speech frequency. Stratified analysis suggested that some high cardiovascular risk participants such as male, age ≥65, exposed to occupational noise, smoker and with diabetes, hypertension or hyperlipidemia had higher risk of stroke. Furthermore, severe or greater hearing loss combined with age, diabetes, hypertension and hyperlipidemia had joint effects on stroke. Conclusions: The results have suggested a dose-response relationship between hearing loss and stroke risk in middle-aged and older adults. Graphical abstract: Image 1 Highlights: Hearing loss levels were associated with stroke or its subtypes prevalence at speech- or high-frequency. Stratified analysis and conjoint analysis at speech- or high-frequency. Hearing loss might be a useful 'marker' to warn people about stroke risk.